Analisis Perencanaan Produksi Minuman Herbal Pada UMKM Liwut Sari: Di Borong Manggarai Timur - Sandriani, Gradiana; Pulinggomang, Yoseba; J.B.B Hattu, Lukas (LPPM Universitas Sains dan Teknologi Komputer, 2025)
This research is a case study with the object of research at UMKM Liwut Sari The purpose of this study is to determine and explain the production planning of herbal drinks at UMKM Liwut Sari. Data collection techniques in this research are observation, interviews, and documentation while data analysis techniques use forecasting and Break Even Point (BEP). The results of the sales forecasting analysis of red ginger herbal drink and temulawak herbal drink at Liwut Sari UMKM in January are predicted to sell 263 packs of red ginger herbal drinks and 262 packs of temulawak herbal drinks, in February red ginger herbal drinks is 271 packs and temulawak herbal drinks is 270 packs, in March red ginger herbal drinks is 279 packs and temulawak herbal drinks is 278 packs. The results of the Break Even Point (BEP) analysis show that if UMKM Liwut Sari produces 86 packs of red ginger herbal drinks or Rp 4,289,855 and 81 packs of temulawak herbal drinks or Rp 4,054,794, then UMKM Liwut Sari does not make a profit or suffers a loss because at that point the company is in a state of principal return.